Acid Ceramidase Deficiency in Mice Results in a Broad Range of Central Nervous System Abnormalities - Sikora, Jakub; Dworski, Shaalee; Jones, E Ellen; Kamani, Mustafa A; Micsenyi, Matthew C; Sawada, Tomo; Le Faouder, Pauline; Bertrand-Michel, Justine; Dupuy, Aude; Dunn, Christopher K; Xuan, Ingrid Cong Yang; Casas, Josefina; et al. (The American journal of pathology, 2017)
Farber disease is a rare autosomal recessive disorder caused by acid ceramidase deficiency that usually presents as early-onset progressive visceral and neurologic disease. To understand the neurologic abnormality, we investigated behavioral, biochemical, and cellular abnormalities in the central nervous system of Asah1P361R/P361R mice, which serve as a model of Farber disease. Behaviorally, the mutant mice had reduced voluntary locomotion and exploration, increased thigmotaxis, abnormal spectra of basic behavioral activities, impaired muscle grip strength, and defects in motor coordination. A few mutant mice developed hydrocephalus. Mass spectrometry revealed elevations of ceramides, hydroxy-ceramides, dihydroceramides, sphingosine, dihexosylceramides, and monosialodihexosylganglioside in the brain. The highest accumulation was in hydroxy-ceramides. Storage compound distribution was analyzed by mass spectrometry imaging and morphologic analyses and revealed involvement of a wide range of central nervous system cell types (eg, neurons, endothelial cells, and choroid plexus cells), most notably microglia and/or macrophages. Coalescing and mostly perivascular granuloma-like accumulations of storage-laden CD68+ microglia and/or macrophages were seen as early as 3 weeks of age and located preferentially in white matter, periventricular zones, and meninges. Neurodegeneration was also evident in specific cerebral areas in late disease. Overall, our central nervous system studies in Asah1P361R/P361R mice substantially extend the understanding of human Farber disease and suggest that this model can be used to advance therapeutic approaches for this currently untreatable disorder.
Keywords: sfingolipidy; myši; centrální nervový systém; Neurons; Acid Ceramidase; Mice, Transgenic; Farberova nemoc; Sphingolipids; fenotyp; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Time Factors; Homozygote; kyselá ceramidasa; Hydrocephalus; Farber Lipogranulomatosis; Phenotype; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; homozygot; Cerebellum; velký mozek; malformace nervového systému; myši transgenní; Central Nervous System; Animals; mozeček; Mice; zvířata; chování zvířat; hydrocefalus; neurony; Motor Activity; časové faktory; Nervous System Malformations; pohybová aktivita; Behavior, Animal; Cerebrum